Secondary School students' engagement in learning Japanese as a second language - Asano-Cavanagh, Yuko; Cavanagh, Rob (AARE, 2009)
The learning of Asian languages is a significant feature of national and state education policies. For example, the multi-million dollar National Asian Languages and Studies in Schools Program which was designed to increase participation and engagement in learning Asian languages. While much of the impetus for this press is due to international trade and economic priorities, the curriculum area of languages other than English is also important for educative and cultural reasons. Of the four Asian languages typically taught in local schools (Indonesian, Japanese Korean and Mandarin), Japanese has the highest enrolment. The research reported in this paper focussed on the engagement of Western Australian secondary school students in their classroom learning of Japanese. While the study of second language instruction and teaching is situated within the field of second language acquisition, it also applies conventional educational theory. For example, cognitive, meta-cognitive and socio-affective constructs. This similarity is reflected in the model of student engagement that informed instrumentation decisions in the investigation of local Japanese classroom learning. Engagement was conceptualised as a function of student capability for learning and the expectations placed on this learning. Capability was defined in terms of self-esteem, self-concept, resilience, self-regulation and self-efficacy. Expectations were defined as facets of learning for understanding – expectations of explanation, interpretation, application and having perspective, empathy and self-knowledge.A self-report instrument was administered to 278 Years Eight to Twelve students. The instrument comprised 50 statements about attributes of students and their learning. Students responded on a four-category response scale. The data were tested against the Rasch rating Scale Model. Data fitting the model shows a uni-dimensional trait was measured and the measure was invariant. Data-to-model fit was assessed by estimation of item difficulty thresholds, individual item fit statistics, the Person Separation Index and Principal Components Factor loadings of residuals. The difficulty students had in affirming individual statements and groups of statements were also estimated to indicate common and less common perceptions of Japanese classroom learning. The results showed a balance between student views of their capability for learning and the expectations of this learning. Engagement was characterised by resilience, self-regulation and self-efficacy. The students affirmed expectations of explanation, interpretation, application and having perspective, empathy and self-knowledge. The perspective and empathy items were more highly affirmed. The empirical findings are discussed in consideration of second language instruction and learning theory. The paper concludes with some recommendations for instrument improvement and future studies.